Exposición Al Material Particulado En Las Áreas De Preparación De Material Abrasivo De Una Empresa En El Parque Industrial De Riobamba - Pérez, Diego Fernando Mayorga; Nuñez, Edwin Fernando Viteri; Landi, María Verónica Albuja; Chávez, Javier Enrique Orna; Sampedro, Otto Fernando Balseca; Reyes, Jorge Isaías Caicedo; Bernal, Catalina Margarita Verdugo (European Scientific Journal, ESJ, 2017)
In this research, a study of the determinants of risk and exposure on a particular matter was done in preparation for the areas of abrasive material. Qualification of chemical risks (inorganic powder) using the matrix triple irrigation was performed. In addition, the dust concentration in each position was evaluated using the rules NIOSH 0500 (total dust) and NIOSH 0600 (respirable dust) by statistical criteria NIOSH. Thus, their results are based on the gravimetric method. A sanitary survey to determine the relationship between the study variables with the powder was also performed. After examining the sampling points, 5 points was obtained with overexposure. As a result, a letter of commitment was made with corrective actions. It also re-monitors those exposed points overexposure resulting in a point (primary crusher). However, this works one to two times per month for 4 hours. As a result, no longer exposure would make production workers rotate jobs. Additional corrective actions, to further reduce exposure to dust extractor main advantage powders, were proposed. This, however, results in the generation of optimal environment for workers.